Review on tax research in accounting: Is the information given by U.S. GAAP income taxes also provided by IFRS? - Lisa Frey; Lisa Engelhard (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2017)
In this paper, we present a review of tax research in accounting. We outline U.S. GAAP accounting rules for the following four income tax notes and survey the area of research literature dealing with the information content provided by U.S. GAAP: (1) unrecognized tax benefits, (2) valuation allowances, (3) foreign earnings designated as permanently reinvested, and (4) book-tax differences. Building on this, we present the accounting rules for comparable income tax notes following IFRS standards and offer which we believe are interesting avenues for future research on the information on tax notes provided by IFRS financial statements.
Keywords: M40; M41; M48; H20; 650; UTB; valuation allowance; permanently reinvested earnings; book-tax difference; U.S. GAAP; IFRS; tax notes